Community structure of zooplankton in seagrass beds in the bay of Balikpapan City, East Kalimantan - Aprilia Kartini Putri; Jailani Jailani; Nurfadilah Nurfadilah (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
Zooplankton is a component in the food chain that has an important role in the production value of an ecosystem, this is because zooplankton is the main connecting link between phytoplankton and nekton. The purpose of this study was to determine the types of zooplankton found in the seagrass beds of Balikpapan Bay and to determine the value of diversity, uniformity and dominance of zooplankton in the waters of Balikpapan Bay. Measurement of water quality parameters was carried out at the Water Quality Laboratory of the Faculty of Fisheries and Marine Sciences. This research was conducted in November - December 2022 in the waters of the Bay of Balikpapan City using the consideration method (Purposive Sampling Method) to determine the research station and use the method Sedgewick Rafter for the identification stage the data were analyzed by calculating zooplankton abundance, diversity index, uniformity index and dominance index, then the data were analyzed using Microsoft Excel. The abundance of zooplankton in the waters of Balikpapan City Bay consisted of 2 classes, namely copepods and oligotrichea, while for the abundance of zooplankton the results were different at station 1, the value was 1134 ind/L at station 2, the result was 567 ind/L and at station 3, the value was obtained 252 ind/L for station 1 and 2 of the highest species is the crime of murderand at station 3 the highest species Tintinnopsis open. The diversity index value in Balikpapan Bay waters is categorized as moderate species, the uniformity index value in Balikpapan Bay waters is categorized as relatively stable and the dominance index value in Balikpapan Bay waters is categorized as no dominant species.